Biomineralization Of Manganese By Bacillus Spp Isolated From A Marine Biofilm - H. Sarvamangala (Society for Mining, Metallurgy & Exploration, 2008)
Biomineralization of manganese on titanium condenser material exposed to seawater has been illustrated. Biom-ineralization occurs when the fouling components, namely, the microbes, are able to oxidize minerals present in water and deposit them as insoluble oxides on biofilm surfaces. Extensive biofilm characterization studies showed that an alarmingly large number of bacteria in these biofilms are capable of oxidizing manganese and are, thereby, capable of causing biomineralization on the condenser material exposed to seawater. This paper addresses studies on understanding the exact role of the microbes in bringing about oxidation of manganese. The kinetics of manganese oxidation by marine Gram-positive manganese oxidizing bacterium Bacillus spp. that was isolated from the titanium surface was studied in detail. Manganese oxidation in the presence of Bacil-lus cells, by cell free extract (CFE) and heat-treated cell free extract was also studied. The study confirmed that bacteria mediate manganese oxidation and lead to the formation of biogenic oxides of MnO2, eventually leading to biomineralization on titanium surface exposed to seawater.